Ledhek Mbarang: Bentuk Pertunjukan Tayub di Desa Dologan Kecamatan Japah Kabupaten Blora - Yunita Rahmawati; Agus Cahyono (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
Ledhek Mbarang is a form of folk art typical of Blora Regency which still survives and develops amidst the currents of modernization and social change. This art is characterized by performances that are performed by moving from house to house, resembling the concept of traveling buskers, but with a strong content of dance, music, and local traditions. This study aims to describe in depth the form of Ledhek Mbarang performance in Dologan Village, Japah District, Blora Regency, including its supporting elements, the performance process, and the challenges faced in its preservation. The research method used is a qualitative method with an ethnochoreological approach, which combines ethnographic studies with dance art analysis. Data were collected through direct observation of the performance, visual documentation, and in-depth interviews with artists, audiences, and local community leaders. The research results show that the Ledhek Mbarang performance comprises several key elements: sound design involving gamelan as musical accompaniment, performers consisting of dancers and gamelan musicians, communicative and interactive dance movements, makeup and costume that reflect traditional identity, and the use of specific props to enhance the performance's expressiveness. The performance typically begins with the beating of drums or jedor (a traditional drum) on the roadside to signal the beginning of Ledhek Mbarang.